METHODS AND RESULTS OF STUDYING THE STRUCTURE AND TINCTORIAL PROPERTIES OF CATGUT THREAD - O. Maksymenko; V. Hryn (Проблеми екології та медицини, 2023)
Suture material used in abdominal surgery must have more or less antigenic properties so that during wound healing it could be destroyed by an immune response to rejection, which is known to involve cytotoxic T-lymphocytes and macrophages. This, in turn, can lead to the development of aseptic peritonitis. Therefore, while planning an experimental simulation of aseptic peritonitis, we decided to use catgut thread as an antigenic stimulation of the local immune system. The aim of our research was to study the morphological criteria of the microscopic structure and tinctorial properties of catgut thread. The material of the research was the sterile catgut thread sized 2/0, 0.3 mm thick, of equal lengths, which we twisted arbitrarily into flat compact globules occupying an area of approximately 1 cm2. In order to carry out a histological examination, some catgut globules were subjected to total staining with a hematoxylineosin solution and subsequent embedding of these globules in a paraffin block and making appropriate sections from it. The other half of the catgut globules were studied using the method of epoxy plastination with the production of grinds with staining by a 1% solution of methylene blue on a 1% borax and without any staining. After the total staining of the catgut globules with a hematoxylin-eosin solution, a clear acidophilic reaction was revealed, which was manifested in the intense pink color. Catgut thread has a non-uniform fibrous structure, in which dark streaks stand out, dividing it into a series of longitudinal, lighter, layered fascicles, which consist of a dense collection of thin fibrillar elements. These fibrillar elements are orderly fascicles of collagen fibers, while the dark streaks are layers of loose fibrous connective tissue. These structures can objectively be indicative of morphological criteria in the microscopic analysis of destructive changes of a catgut implant in the peritoneal cavity in an experimental animal.